Overcoming Short Gaps in Peripheral Nerve Repair: Conduits and Human Acellular Nerve Allograft. (June 2014) - Isaacs, Jonathan; Browne, Timothy
Nerve conduits and acellular nerve allograft offer efficient and convenient tools for overcoming unexpected gaps during nerve repair. Both techniques offer guidance for migrating Schwann cells and axonal regeneration though utilizing very different scaffolds. The substantially greater amount of animal and clinical data published on nerve conduits is marked by wide discrepancies in results that may be partly explained by a still poorly defined critical repair gap and diameter size. The available information on acellular allografts appears more consistently positive though this tool is also hampered by a longer but also limited critical length. This article reviews the current relative literature and examines pertinent parameters for application of both acellular allograft and nerve conduits in overcoming short nerve gaps.